Em busca da palavra mais engenhosa: cognição e processamento automático de língua natural com Codenames - Roberta Queiroz Lessa Viola (2021)
Codenames is a game that demands one player to give a word as a clue that relates to other two or three words on the board, and other players to guess the target words. This clue has to be THE word, an specific one that comprises the targets and excludes the bad words on the board. We propose an adapted model of [Koyyalagunta et al., 2021] for that task, in Brazilian Portuguese. Our agents, developed for the role of Codemaster and Guesser, achieved competitive win rates and interesting examples of clues for the game. The given clues and the cognitive processes involved on the game were analized by us.